Recommendations for the Use of Ozone Technology in Post-Harvest Handling to Improve Food Security - Tetelepta, Edward G.; Salakory, Melianus; Ansiska, Paisal (International Journal of Applied Research and Sustainable Sciences, 2023)
Harvest and post-harvest processes are crucial in agriculture, with ozone and irradiation technologies offering sustainable solutions to extend shelf life, reduce spoilage, and enhance food security and competitiveness. The research focuses on determining ozone's impact on vegetable freshness, providing implementation recommendations. Pattimura University's lab experiment on Gnetum gnemon L. leaves evaluates ozone tech for vegetable preservation. Factors include ozone dosage and treatment duration. Data will undergo univariate and SWOT analysis. Research findings indicate that applying ozone at 3 ppm for 25 minutes preserves Gnetum gnemon L. freshness. Implementing ozone in Ambon's food resilience involves education, infrastructure, certification, marketing, and government support.